Effect of Transumbilical Single-Port Laparoscopic-Assisted Duhamel Operation on Serum CRP and IL-6 Levels in Children with Hirschsprung’s Disease - Wang, Miao; Pang, Wenshuai; Zhou, Lixia; Ma, Jiansu; Xie, Shasha (Journal of healthcare engineering, 2022)
Objective. To explore the clinical intervention effect of transumbilical single-port laparoscopic-assisted Duhamel operation on children with Hirschsprung’s disease (HD) and to analyze the effect of treatment on children with serum C-reactive protein (CRP) and interleukin-6 (IL-6) effects. Methods. Retrospectively select 80 children with HD who underwent surgery in our hospital from May 2017 to May 2020 as the research subjects and they are classified as group A according to the difference of the children’s surgical procedures (receiving transumbilical single-port laparoscopic-assisted Duhamel surgery, 40 cases) and group B (receiving conventional laparoscopic surgery, 40 cases), compare the perioperative period (operating time, intraoperative blood loss, surgical posthospitalization, and postoperative gastrointestinal function recovery time), early postoperative complications (perianal dermatitis, urinary retention, enterocolitis, and anastomotic leakage), and late postoperative complications (anastomotic stenosis, dirty stool, recurrence of constipation, and enterocolitis), compare the differences in the levels of CRP and IL-6 between the two groups of children before and after the operation, and conduct a 1-year follow-up of the two groups of children to compare the long-term defecation status. Results. The surgical time of children in group A, postoperative hospitalization time, and postoperative gastrointestinal function recovery time were significantly shorter than those of group B, and the differences between groups were statistically significant (P<0.05). A group of patients: the total incidence of postearly complications was 5.00% lower than 22.50% (P<0.05) in group B (P<0.05), and the total incidence of previous complications after group A of patients was 10.00% lower than 27.50% of group B (P<0.05). The two groups of serum CRP and IL-6 in two groups were not statistically significant (P>0.05), and the serum CRP and IL-6 levels of children in group A after surgery were 3 days. It is obviously lower than those in group B, and the differences between groups have statistical significance (P<0.05). At 1 month after surgery, the average bowel movement time in group A is significantly lower than those of group B (P<0.05); during the 1–12 months, the difference between the defecation frequency group of the group A and group B did not have statistically significance (P>0.05). Conclusion. Transumbilical single-port laparoscopic assistant Duhamel operation of HD has a good intervention effect, compared to traditional laparoscopic surgery, the operation time, postoperative hospitalization time, and postoperative gastrointestinal function recovery time, and also help to reduce postoperative near-long complications The incidence improves the stress reactions and long-term defecation functions in children.